Studying the ARP Spoofing Attack Effect on SDN Networks - معلا بشرى; عبد الحميد محمد (Latakia University Journal -Engineering Sciences Series, 2020)
The mapping of Layer 3 (IP) to Layer 2 (MAC) addresses is a key service in IP networks, and is achieved via the Address Resolution Protocol (ARP) protocol in IPv4. Due to its stateless nature and lake of authentication, ARP is an easy goal to spoofing attacks, which can enable Denial of Service (DoS) or Man-in-the-Middle (MIM) attacks. In this search, we discuss the problem of ARP spoofing in the context of Software Defined Networks (SDNs). We studied important parameters such as throughput, delay and the availability of the network. Results showed that ARP spoofing attacks was able to make a negative effects on network performance.